Biodistribution of 99mTc-HSA-nanoparticle in Lymphatic Node of Animal Model Induced by 7,12 Dimethylbenz(a)anthracene - Rizky Juwita Sugiharti; Iim Halimah; Isa Mahendra; Witri Nuraeni; Maula Eka Sriyani; Eva Maria Widyasari (Indonesian Journal of Pharmaceutical Science and Technology, 2019)
Breast cancer is one of the most common malignant tumors found in women and hasbecome as the second cause of death in women after cervical cancer.We successfully synthesizedtechnetium-99m labeled Human Serum Albumin nanoparticle(99mTc-HSA nanoparticle); a radiopharmaceuticalwhich potentially used for application in lymphoscintigraphytechnique for tracing lymphatic system.This study was aims to obtain pre-clinical data from 99mTc-HSA nanocolloidin Sprague Dawleyfemale ratsgiven7, 12-dimethylbenzeneanthracene (DMBA) - induced cell proliferation in the breast tissues.The rats are divided into two groups, one groupsaregiven DMBA and observed for 5, 8 and 12 weeks and the other group is without any treatment as control.Biodistribution study of 99mTc-HSA nanoparticlewas conducted to identify the accumulation of this agent in the popliteal and lumbar lymph nodes and the other tissuecompare to normal rats. 99mTc-HSA nanoparticleshown good accumulation in popliteal lymph node 2.90+1.32 %ID; 0.81 + 0.47 %IDand 1.04+0.46 %ID at one hour post injectionin 5, 8 and 12 weeks respectively.The popliteal extraction (PE) was estimated with value 87.92 %, 74.07%, 71.79% in 5, 8 and 12 weeks respectively. This result showed that99mTc-HSA nanoparticleis very promising compound to be lymphoscintigraphyagentin detection of breast cancer.Key words: lymphoscintigraphy, 99mTc-HSA nanoparticle, breast cancer